A strategic profit model: measuring Indian apparel retail performance - Selvarasu, A. (2014)
The strategic profit model (SPM) has been used to measure the performance of three Indian retail companies that focus in apparel. In the study three companies have been chosen to represent three groups of companies viz., large, medium and small corporate. In the case of large size, medium size and small size corporate, Pantaloon retail is considered with a turnover of Rs.3,031 crores, Shoppers’ stop retail with a turnover of Rs.849 crores and Provogue with a turnover of Rs.228 for the year 2007 have been included for the study, respectively. In order to find out the suitable strategies for the companies in the categories, the comparison has been done with its best performance as well as the indicators in relation to peer averages. The ROA has been noticed around 5 percent and the study attempt to reveal the appropriate strategy to increase it by 10 percent. The study has been carried out to indicate suitable strategies to maximize the performance in the future years for Indian apparel retail sector in line with the measure of RONW.